Helium gas-gap heat switch for Sub-Kelvin refrigeration system. Issue 1 (1st May 2022) - Xi, Xiaotong; Yang, Biao; Gao, Zhaozhao; Chen, Liubiao; Zhou, Yuan; Wang, Junjie
Abstract: The heat switch is an indispensable thermal control device in the low-temperature system. The helium gas-gap heat switch plays a key role in Sub-Kelvin sorption coolers and adiabatic demagnetization refrigerators, and its effective switching between thermal conducting (ON state) and insulating (OFF state) is achieved by changing the pressure of the gas in the gap. In this paper, a 4 He gas-gap heat switch was designed. And the thermal characteristics at different cold block temperatures were experimentally tested, which provides a reference for the development of high-efficiency gas-gap heat switches.